Narrative Review of Glycemic Management in People With Diabetes on Peritoneal Dialysis - Steve Bain (Kidney International Reports, 2023)
There is an increasing number of people with diabetes on peritoneal dialysis (PD) worldwide. However, there is a lack of guidelines and clinical recommendations for managing glucose control in people with diabetes on PD. The aim of this review is to provide a summary of the relevant literature and highlight key clinical considerations with practical aspects in the management of diabetes in people undergoing PD. A formal systematic review was not conducted because of the lack of sufficient and suitable clinical studies. A literature search was performed using PubMed, MEDLINE, Central, Google Scholar and ClinicalTrials.gov., from 1980 through February 2022. The search was limited to publications in English. This narrative review and related guidance have been developed jointly by diabetologists and nephrologists, who reviewed all available current global evidence regarding the management of diabetes in people on PD.We focus on the importance of individualized care for people with diabetes on PD, the burden of hypoglycemia, glycemic variability in the context of PD and treatment choices for optimizing glucose control. In this review, we have summarized the clinical considerations to guide and inform clinicians providing care for people with diabetes on PD.